Experience and results of laparoscopic inguinal herniorrhaphy (2017)
Introduction: Due to the invention of minimally invasive surgery, inguinal hernia repair by laparoscopy has become a common procedure. This paper presents the results of 92 inguinal hernia repairs by laparoscopy performed using the transabdominal pre-peritoneal technique (TAPP) between August 2001 and January 2014.Objective: To present our results regarding recurrence rate, postoperative pain and need for conversion.Materials and methods: The results of the procedure using TAPP were retrospectively analyzed based on an average follow-up time of 8 years.Results: Three (3.2%) cases required conversion, three (3.2%) were recurrent and six (6.4%) presented chronic pain.Conclusion: Laparoscopic hernia repair by TAPP is a safe procedure. Effectiveness and complication rates have shown to be similar to open and TEP techniques.